SEX EDUCATION IN SCHOOLS: WHEN THE EASIEST THING IS SILENCE (Interdisciplinary Studies Journal, 2024)
Sex education is a taboo subject in schools. It is not talked about directly, but it is extremely present in everyday school life. Officially in Brazil, Sex Education is a cross-curricular theme, as set out in the National Curriculum Parameters of 1996 and, during the conservative ascendancy in the federal government, its omission from the main legal provisions of this period (between 2016 and 2022). In schools, Sex Education has been introduced with a biological, hygienist bias, mainly stemming from health projects. In this article, we will report on a training activity with sixth-grade students at a school in the metropolitan region of Rio Grande do Sul, using the Adolescent Health Handbook. To this end, we will carry out qualitative research using experience reports and documentary analysis based on feminist epistemology and gender studies. The results point to the need for greater theoretical depth, not just for education professionals, but for society as a whole, on the essential cultural, historical and social nature of Sex Education, as well as the internal nature of the school's Sexuality Pedagogy.
Keywords: Sex Education; Gender and Sexuality; Teacher Continuous Training